Limit cycle dynamics of the gymnastics longswing - Vicinanza, D.; Newell, K. M.; Irwin, G.; Smith, L.; Williams, G. K. R. (Human Movement Science, 2018)
The purpose of the study was to examine the macroscopic dynamics of the longswing through a limit cycle analysis of the motion of the center of mass (CM) as a function of skill level. One elite international, five gymnasts able to perform release and regrasp skills, five gymnasts unable to perform release and regrasp skills, and five novice gymnasts each performed four consecutive longswings on a high bar. Kinematic data were collected to facilitate the calculation of the center of mass position of the performer during swinging. Poincare plots were used to explore the limit cycle dynamics of the center of mass movement. The attractor dynamic was very close to a onedimensional limit cycle for the elite (D=1.18) but higher for the release and regrasp group (D=1.35 ± 0.06) and non-release and regrasp group (D=1.37 ± 0.07). The novice dynamic was characterized by a two-dimensional limit cycle (D=2.49 ± 0.28) that also had more variability and lower determinism. In the frequency domain, Inharmonicity was lower and the Q factor higher as a function of increased skill level. The findings show that the dynamical degrees of freedom of the CM in the skilled performance were reduced compared to those of novices and represented a more efficient and predictive, rather than exploratory, technique. AUTORREFERAT